Effect of Desliming of Tailings on the Fresh and Hardened Properties of Paste Backfill Made from Alkali-Activated Slag - Ferdi Cihangir; Yunus Akyol (Advances in Materials Science and Engineering)
Cemented paste backfill (CPB) allows environmental friendly management of potentially hazardous tailings generated from milling of nonferrous metal sulphide ores by placing such tailings into the underground mined-out openings. The components of CPB are tailings, water, and binders. These components significantly affect the physicomechanical, workability, and geotechnical properties of CPB. Ordinary Portland cement (OPC) is the commonly used binder for CPB operations. The effects of the tailings characteristics and OPC are extensively studied in the study area. The beneficial effect of the use of alkali-activated slags (AASs) on the mechanical and durability properties of CPB of sulphide-rich tailings has been recently reported. Therefore, this study especially focused on the effect of desliming of the tailings on the workability properties of sulphide-rich tailings CPB containing AAS besides hardened properties. In this scope, the water-retention capacities of full (FT) and deslimed tailings (DT) and the workability characteristics of CPB mixtures were studied. DT was found to decrease the water-retention capacity, leading to denser CPB mixtures. In addition, DT-AASs usage produced no adverse effect on the workability of fresh CPB materials. LSS-S (slag activated with liquid sodium silicate) improved the flowability of CPB mixtures owing to its dispersant effect. Desliming also modified the tailing properties by removing fine particles and improved the main geotechnical parameters of CPB.